Founder's diversification - McFarlan, F. Warren (SAGE knowledge. Cases., 2016)
August 6th, 2010, Founder Group Chairman, Wei Xin, sat in his office, reflecting on the afternoon's media session. Two days ago, Founder and Acer Group had jointly announced that Acer would rent 70 million USD worth of Founder PCs for 7 years, and be responsible for a majority of Founder's PC business, along with its related departments and employees. This news triggered heated discussions in the media, as many people were surprised. To dispel confusion, Wei and Vice President Fang Zhonghua held a public media session where Wei expressed Founder Group's strategic intentions. In 2009, the PC business had sold 3,000,000 units, had sales revenues of 6.5 billion RMB, and was #4 in domestic market share. This case study examines this topic.